Assessing and addressing climate-induced risk in Sub-Saharan rainfed agriculture - Cooper, Peter J.M.; Coe, R.; Stern, RD (Cambridge University Press, 2011)
Rainfed agriculture in sub-Saharan Africa (SSA) is the mainstay of the continent's food and feed production. Nearly 90% of staple food and feed production comes from, and will continue to come from, rainfed agriculture (Rosegrant et al., 2002). In spite of this, investment in this vital production system, and hence its productivity, has stagnated. There are many complex and interrelated issues that contribute to this state of affairs. The outcomes of lack of investment and low production of rainfed agriculture reinforce each other leading to poverty traps and increased vulnerability of livelihoods to climatic and other shocks (World Bank, 2000). This has become well recognized and an emerging political will, both within and outside SSA, to support increased investment in rainfed agriculture appears to be gaining momentum (Sanchez et al, 2009).